PENGARUH STRUKTUR DESENTRALISASI, PARTISIPASI ANGGARAN DAN ORIENTASI NILAI MANAJER PADA INOVASI TERHADAP KOMITMEN ORGANISASI PADA INDUSTRI PERBANKAN DI ACEH - Rahmadani, Ika (Universitas Pendidikan Indonesia, 2017)
Abstract: The objective of this study are to eximine the influence of decentralised sturcture, budgetary participation, managers value orientation towards innovation on organisational commitment. The respodents were middle level managers in Acehâ€™s banking industry. Out of 131 questionnaires distributed, 118 can be used for analysis. Using Regression Analysis, the result of this study indicates that the decentralised structure and managers value orientation towards innovation have a negative influence to organisational commitment. Meanwhile, the budgetary participation has a positive and significant influence to organisational commitment. Recomendation for the future research is to use other variable such as organisational culture or job satisfaction to see its colleration to organisational commitment.Â Â